The Effect of Integrating Family Planning with a Maternal and Newborn Health Program on Postpartum Contraceptive Use and Optimal Birth Spacing in Rural Bangladesh. Issue 3 (8th September 2015) - Ahmed, Saifuddin; Ahmed, Salahuddin; McKaig, Catharine; Begum, Nazma; Mungia, Jaime; Norton, Maureen; Baqui, Abdullah H.
<x xml:space="preserve">Abstract</x> Meeting postpartum contraceptive need remains a major challenge in developing countries, where the majority of women deliver at home. Using a quasi‐experimental trial design, we examine the effect of integrating family planning (FP) with a community‐based maternal and newborn health (MNH) program on improving postpartum contraceptive use and reducing short birth intervals <24 months. In this two‐arm trial, community health workers (CHWs) provided integrated FP counseling and services during home visits along with their outreach MNH activities in the intervention arm, but provided only MNH services in the control arm. The contraceptive prevalence rate (CPR) in the intervention arm was 15 percent higher than in the control arm at 12 months, and the difference in CPRs remained statistically significant throughout the 24 months of observation. The short birth interval of less than 24 months was significantly lower in the intervention arm. The study demonstrates that it is feasible and effective to integrate FP services into a community‐based MNH care program for improving postpartum contraceptive use and lengthening birth intervals.